Circus - Ehlert, Lois. ([New York, NY] : HarperCollins, 1992)
Leaping lizards, marching snakes, a bear on the high wire, and others perform in a somewhat unusual circus.
Keywords: Circus -- Fiction; Animals -- Fiction